Africa’s growing risk of diseases that spread from animals to people - Bett, Bernard; Randolph, Delia; McDermott, John (2020)
The outbreak of the novel coronavirus (COVID-19) is a rude awakening to many who believed the era of infectious disease was over. In this post, Bernard Bett, Delia Randolph and John McDermott argue that not only are pandemics not over, they may be increasing in frequency; and while most originated in Asia in the past, Africa may be poised to become an important source of so-called “zoonotic pathogens”—with its population growth, rapid urbanisation, and rising global integration offering promising vectors for outbreaks.